Preconditions of Assimilation and the Choice of School: Comparison Between Groups of Parents of the First-Graders - Leončikas, Tadas (Sociologija. Mintis ir veiksmas, 2006)
The article assesses social aspects of ethnicity through analysis of differences exhibited by those who choose different primary schools (there are sectors of educational system in Lithuania that differ in language of instruction – Lithuanian, Russian, or Polish) for their children. On the basis of 2005 survey data, the groups of parents are found to differ with regard to basic social characteristics. Assimilation prospects are seen as related to strategies of social mobility. It is concluded that school cannot be considered an independent factor in assimilation process. The choice of a school is the result of parents’ integration and of their assimilative attitudes rather than the other way round. Having assessed ethnic diversity of first-graders’ parents, the conclusion is made that the Russian language as such and schools with instruction in Russian tend to accommodate a larger share and spectrum of the non-Lithuanian population than the analogous Lithuanian institutes.
Keywords: ethnicity; education; assimilation; school